Tinjauan Etika dan Governance Pada Bisnis Halal Di Indonesia - Kurniati, Pratiwi; Atiqah, Nur (Jurusan Akuntansi, Fakultas Ekonomi dan Bisnis, Universitas Tanjungpura, 2021)
Halal and haram become sensitive and interesting issues because the obligation of a Muslim is bound by shari'ah law in its activity. The issue of prohibition of food, beverage and medicinal products has been on the rise several times in Muslim societies, as in the case of 2000, Indonesian Muslims were overwhelmed with Monosodium Glutamate (MSG) products in their production process using a catalyst from Bactosoytone containing pig enzymes, issued a fatwa to revoke the product from circulation and declare haram for consumption.After that, 2016 was raised again the case with the bakery products of famous brands in Indonesia, which before the product has been labeled halal, was circulated on the prohibition of the materials used in the manufacture of some types of their cakes. This creates anxiety for the people of Indonesia, especially Muslims.This study aims to describe about ethical theory and good corporate governance in Islam and describe its implications for violations of ethics and governance in sharia business and offer solutions and ways to overcome them. This research is descriptive research by using library research approach (library research). By describing the theory of ethics and governance then its implications for the impact of the problem of violations of halal business in Indonesia, and formulate solutions in the matter.In this study, the authors also offer the implementation of CSR on certification assessment that must be passed in 3 levels of Halal Product, Responsible Halal Product, Responsible Halal Business. It will motivate business people to fulfill these three levels, so that businesses that have ethics and good corporate governance and achieve the level of Islam, Faith, and Ihsan in business.Â